Termodinâmica estatística de líquidos com o método de Monte Carlo. I. Metodologia - Barlette,Vania Elisabeth (1999)
Statistical mechanics Monte Carlo simulation is reviewed as a formalism to study thermodynamic properties of liquids. Considering the importance of free energy changes in chemical processes, the thermodynamic perturbation theory implemented in the Monte Carlo method is discussed. The representation of molecular interaction by the Lennard-Jones and Coulomb potential functions is also discussed. Charges derived from quantum molecular electrostatic potential are also discussed as an useful methodology to generate an adequate set of partial charges to be used in liquid simulation.